On The Solutions Of Quasi – Lyapunov Operator Equations (Al-Mansour Journal, 2022)
In this paper, some theorems are modified to ensure the existence and uniqueness of the solution for the Quasi –Lyapunov operator equation.Also, the range of the Quasi – Lyapunov equation is studied. As well as, the nature of the solution for the Quasi –Lyapunov operator equation is studied for special types of operators.
Keywords: Lyapunov equations; Sylvester equation; Linear operator equations; Sylvester – Rosenblum Theorem.